More than a simple storage organ: Adipose tissue as a source of adipokines involved in cardiovascular disease - Rega-Kaun, Gersina; Kaun, Christoph; Wojta, Johann (Thrombosis and Haemostasis, 2013)
Overweight and obesity in many countries have developed into a serious health problem by themselves and by their impact on other pathologies such as insulin resistance, type 2 diabetes, hypertension, heart disease and cancer. The modulation of these diseases by adipose tissue-derived biomolecules, so-called adipokines, could be the key to differentiate between metabolically healthy and unhealthy obesity. This review will discuss the pathophysiological role of selected adipokines, primarily focusing on cardiovascular diseases. Furthermore, we will highlight possible therapeutic approaches, which target these biomolecules.
Keywords: Obesity; atherosclerosis; thrombosis